2020
DOI: 10.3389/fnins.2020.595664
|View full text |Cite
|
Sign up to set email alerts
|

Deeper and Deeper on the Role of BK and Kir4.1 Channels in Glioblastoma Invasiveness: A Novel Summative Mechanism?

Abstract: In the last decades, increasing evidence has revealed that a large number of channel protein and ion pumps exhibit impaired expression in cancers. This dysregulation is responsible for high proliferative rates as well as migration and invasiveness, reflected in the recently coined term oncochannelopathies. In glioblastoma (GBM), the most invasive and aggressive primary brain tumor, GBM cells modify their ionic equilibrium in order to change their volume as a necessary step prior to migration. This mechanism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
2
14
0
1
Order By: Relevance
“…These changes may have consequences for the level of growth control, cell volume and activity regulation in cancer cells. [52][53][54] Nevertheless, the interpretation of these results requires further experiments.…”
Section: Cellular Uptake By Pixementioning
confidence: 96%
“…These changes may have consequences for the level of growth control, cell volume and activity regulation in cancer cells. [52][53][54] Nevertheless, the interpretation of these results requires further experiments.…”
Section: Cellular Uptake By Pixementioning
confidence: 96%
“…In fact, alterations in Em (depolarization or hyperpolarization) have been proposed to play a crucial role in controlling the cell cycle, thus suggesting a relevance of BK channel in cancer proliferation, invasion, and metastasis [ 12 ]. In this regard, in some studies, activation of BK channels has been reported to slow proliferation and invasion of breast cancer cells, or in glioblastoma cells [ 11 , 13 , 14 , 15 , 16 ]. In contrast, in other studies, anti-cancer action has been described for inhibition of BK channels, namely, in metastatic breast cancer cells, as well as in endometrial cancer cells [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, potassium-stimulated depolarization facilitates Ca 2+ entry through T-type (low depolarization potential) or L-type (higher depolarization potential) channels [ 33 ]. On the other hand, calcium-activated potassium channels (BK channels), stimulated by Ca 2+ or Mg 2+ , are responsible for the majority of K + conductance throughout the cell membrane [ 34 , 35 ]. In MB, voltage-gated potassium channel EAG2 is upregulated in human-derived MB cells, where it promotes tumour growth in vitro [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%